ANALISIS PENYIMPANAN ARSIP AKTIF DI BIRO PEMERINTAHAN DAN OTONOMI DAERAH SEKRETARIAT DAERAH PROVINSI JAWA TIMUR - Salsabilla, Sania Salma; arlupi utami, dian (Jurnal Inovasi Administrasi Negara Terapan, 2023)
Archives are a from of carrying out activities that contain important information as information material that must be stored and cared for properly in an institution or organization. This study aims to analyze the storage of active archives at the Bureau of Government and Regional Autonomy at thr Regional Secretariat of East Java Province. This study uses the theory of archive storage procedures presented by Sugiarto dan Wahyono which includes checking,indexing, marking, sorting adn storing. This type of research is descriptive research with a qualitative approach. Data collection techniques were carried out by observation, interviews and documentation. The results of the study explain that at the inspection stage it has not been carried out thoroughly to check on each sheet of document because there are no special employees in managing archives, indexing is carried out by determining catch words to be used as a storage system namely using a number system, marking that coding has not been implemented or marking with dashes or circle on catch word that have been determined due to lack of understanding of employees in carrying out this stage, sorting is carried out by grouping documents based on a predetermined storage system, storing is carried out by storing documents according to the specified storage system however, the facilities and infrastructure provided are still limited in number. The recomended suggestions are to make arrangements related to active archives storage procedures, to appoint employees in the archive field, training is needed in the archive field and to increase the procurement of facilities and infrastructure used in the active archive storage process. Keywords: Analytics, Active Archives, Storage